2022
DOI: 10.3389/fphar.2022.870221
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Immune-Related Long Noncoding RNA Prognostic Signature and Inflammatory Microenvironment for Cervical Cancer

Abstract: Purpose: Our research developed immune-related long noncoding RNAs (lncRNAs) for risk stratification in cervical cancer (CC) and explored factors of prognosis, inflammatory microenvironment infiltrates, and chemotherapeutic therapies.Methods: The RNA-seq data and clinical information of CC were collected from the TCGA TARGET GTEx database and the TCGA database. lncRNAs and immune-related signatures were obtained from the GENCODE database and the ImPort database, respectively. We screened out immune-related lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…In recent years, in-depth studies have developed a mass of immune-related prognostic signatures to predict immunotherapy response and have investigated the relationship between immune landscape and prognosis in CC [46][47][48][49][50]. For instance, Yu et al [51] established an immune infiltration-based signature and demonstrated that a better prognosis in CC patients seemed to be relatively immune-inflamed with greater immune cell infiltration, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, in-depth studies have developed a mass of immune-related prognostic signatures to predict immunotherapy response and have investigated the relationship between immune landscape and prognosis in CC [46][47][48][49][50]. For instance, Yu et al [51] established an immune infiltration-based signature and demonstrated that a better prognosis in CC patients seemed to be relatively immune-inflamed with greater immune cell infiltration, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, compared to other models with similar prediction abilities, our signature contains the least number of lncRNAs and is relatively easy to be applied in clinical practice [41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the tumor microenvironment (TME), as an intrinsic oncogenic mechanism and epigenetic modification, has become a research hotspot [ 35 ]. The TME contains a few non-cancerous cells that influence cancer cell survival and has a significant effect on tumor metastasis and drug treatment efficacy [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%